Primer on the Cluster Impact on Internationalisation in the Form of FDI in the Time of Industry 4.0 - Götz, Marta (European Spatial Research and Policy, 2020)
The novelty of Industry 4.0 (I4.0) as a research topic means that the literature covering the interrelations between digital business transformation and categories such as internationalisation, foreign direct investment (FDI), or clusters is scant. This paper shows that clusters may contribute to the advancement of I4.0 while at the same time they stimulate the internationalisation of indigenous firms and the inflow of foreign investors. Based on conceptual deliberations it develops a research agenda for exploring how clusters might affect OFDI and IFDI by facilitating the I4.0. It can advance our understanding on the spatial aspects of the ongoing business digital transformation.